HUBUNGAN PENGETAHUAN DAN SIKAP IBU TERHADAP KUNJUNGAN IBU BALITA DI KELOMPOK BINA KELUARGA BALITA (BKB) MELATI INDAH DESA TOAPAYA SELATAN KECAMATAN TOAPAYA KABUPATEN BINTAN PROVINSI KEPULAUAN RIAU - Elinda, Elinda; Yunifitri, Astri; Suryanti, Suryanti (Universitas Batam, 2020)
Malnutrition problem is the main focus of the President of Indonesia. In this case President Joko Widodo and World Bank President Jim Yong Kim discussed the stunting problem or malnutrition which reached number of children in the country. Malnutrition in the Riau Islands Province in 2017 was a parental problem (63.4%). One of a series of sustained and guided activities to ensure optimal growth and development of infants rolled out by the government is the